PENGARUH KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA PENGAJAR PADA GANESHA OPERATION CABANG KOTA PONTIANAK - B31111108, Febrian Arie Waspodo (Jurnal Manajemen Update, 2016)
This research aims to find out about how much influence of the compensation and job characteristics on job satisfaction of teachers at Ganesha Operation Branch Pontianak in West Kalimantan.   This type of research is descriptive and verification, this kind of research is to explain that give causal explanations among the variables, by testing the hypothesis through questionnaires and interviews as technique of collecting  data.the sample in this study is teachers at Ganesha Operation Branch Pontianak with 53 respondents. The analysis technique used in this research is multiple linear regression analysis to determine the effect of each independent variable on the dependent variable and data processing used SPSS version 16.0.   Based on the results of the study revealed that the compensation is partially significant influenced on job satisfaction. The results also revealed that job characteristics partially significant influenced on job satisfaction.   Keywords: compensation, job characteristics, and job satisfaction